The associations of anthropometric, behavioural and sociodemographic factors with circulating concentrations of IGF‐I, IGF‐II, IGFBP‐1, IGFBP‐2 and IGFBP‐3 in a pooled analysis of 16, 024 men from 22 studies. Issue 12 (4th April 2019) - Watts, Eleanor L.; Perez‐Cornago, Aurora; Appleby, Paul N.; Albanes, Demetrius; Ardanaz, Eva; Black, Amanda; Bueno‐de‐Mesquita, H. Bas; Chan, June M.; Chen, Chu; Chubb, S.A. Paul; Cook, Michael B.; Deschasaux, Mélanie; et al.
Abstract : Insulin‐like growth factors (IGFs) and insulin‐like growth factor binding proteins (IGFBPs) have been implicated in the aetiology of several cancers. To better understand whether anthropometric, behavioural and sociodemographic factors may play a role in cancer risk via IGF signalling, we examined the cross‐sectional associations of these exposures with circulating concentrations of IGFs (IGF‐I and IGF‐II) and IGFBPs (IGFBP‐1, IGFBP‐2 and IGFBP‐3). The Endogenous Hormones, Nutritional Biomarkers and Prostate Cancer Collaborative Group dataset includes individual participant data from 16, 024 male controls (i.e. without prostate cancer) aged 22–89 years from 22 prospective studies. Geometric means of protein concentrations were estimated using analysis of variance, adjusted for relevant covariates. Older age was associated with higher concentrations of IGFBP‐1 and IGFBP‐2 and lower concentrations of IGF‐I, IGF‐II and IGFBP‐3. Higher body mass index was associated with lower concentrations of IGFBP‐1 and IGFBP‐2. Taller height was associated with higher concentrations of IGF‐I and IGFBP‐3 and lower concentrations of IGFBP‐1. Smokers had higher concentrations of IGFBP‐1 and IGFBP‐2 and lower concentrations of IGFBP‐3 than nonsmokers. Higher alcohol consumption was associated with higher concentrations of IGF‐II and lower concentrations of IGF‐I and IGFBP‐2. African Americans had lower concentrations of IGF‐II, IGFBP‐1, IGFBP‐2 and IGFBP‐3 and Hispanics had lower IGF‐I, IGF‐II and IGFBP‐3 than non‐Hispanic whites. These findings indicate that a range of anthropometric, behavioural and sociodemographic factors are associated with circulating concentrations of IGFs and IGFBPs in men, which will lead to a greater understanding of the mechanisms through which these factors influence cancer risk. Abstract : What's new? In many cancers, evidence points to insulin‐like growth factors and their associated binding proteins as a possible culprit. This study investigated how IGF and IGF binding proteins correlate with various other cancer‐associated factors. The authors obtained data from 16, 000 cancer‐free males ranging in age from 22 to 89 years. Their analysis confirmed associations between circulating IGFs and IGFBPs and age, race/ethnicity and BMI. They also uncovered some new associations, including with height, drinking alcohol and smoking. IGFs and their binding proteins, they suggest, may be part of the mechanism by which these factors influence cancer risk.